ROOTS: A CRITICAL LINK BETWEEN SOIL-ROOT INTERACTIONS. - Ranvijay Singh, Ajoy Singh*and C.S.Singh (Chelonian Research Foundation, 2024)
Roots are important for plants as they not only provide access to water, but also the nutrients needed for optimum productivity. Roots form symbiotic relationships with other microorganisms in the rhizosphere, acclimate the plant to soil and act as a storage organ. An increase in crop productivity is dependent on the accessibility of appropriate growing conditions in the soil, where oxygen is the crucial component for the performance of root respiration and metabolic activities. The spatial arrangement of root components within the soil is described as root architecture and regulates the soil exposition of the plant. Soil strength limits root growth and can affect gradual root development. Soil penetration resistance is one of the main soil properties, mainly influenced by soil moisture, regulating root elongation and water availability. Soil-root interactions are the critical components of nutrients cycles because all water and nutrients absorbed by the plant should be transported through the rhizosphere. Roots have to attain many different roles at the same time, within the plasticity of the root system, specific root segments change their function during ontogeny. The efficacy of fine root function is firmly related to the architecture of the root system. In this review, we study the sensitivity of root architecture in rooting environments to different types of soil compaction and thoroughly examine the various root adaptations reported in the literature to establish whether root selection and breeding is a viable method of increasing agricultural yields and adaptability in specific climatic conditions. Keywords: Soil-root interaction; root system architecture (RSA); soil strength; rhizosphere; root elongation.